Entrepreneurial learning: the transmitting and embedding of entrepreneurial behaviours within the transgenerational entrepreneurial family. Issue 5 (27th May 2021) - Clinton, Eric; McAdam, Maura; Gamble, Jordan Robert; Brophy, Martina
ABSTRACT: The aim of this paper is to explore how entrepreneurial behaviours are transmitted and embedded across generations within a Transgenerational Entrepreneurial Family (TEF). Although extant family business research has acknowledged the importance of learning in facilitating the transference of values, norms and attitudes, we know little about how learning embeds entrepreneurial behaviours at the family level. In order to address this, we adopted a longitudinal perspective of four TEF cases, drawing on numerous interviews, archival sources and observational instances. An iterative procedure for data analysis, which involved open coding, within-case analyses, second-order coding and cross-case analysis, was undertaken. Our findings illustrate how the implementation of entrepreneurial behaviours within TEFs was a process of negotiation and reification, informed by differences among families in response to critical incidents. Furthermore, we demonstrate how the presence of entrepreneurial behaviour enablers in each TEF has facilitated the perpetuation of entrepreneurial behaviours. Finally, we illuminate the importance of unlearning, the disregarding of prior learning to accommodate new information and behaviours, in the TEF context, where such entities are faced with unlearning paradoxes that subsequently influence their entrepreneurial behaviours.